Chronotropic index during 6-minute walk and acute respiratory events in COPDGene. (April 2022) - Macdonald, David M.; Palzer, Elise F.; Abbasi, Asghar; Baldomero, Arianne K.; Bhatt, Surya P.; Casaburi, Richard; Connett, John E.; Dransfield, Mark T.; Gaeckle, Nathaniel T.; Mkorombindo, Takudzwa; Rossiter, Harry B.; Stringer, William W.; et al.
Abstract: Background: Lower heart rate (HR) increases during exercise and slower HR recovery (HRR) after exercise are markers of worse autonomic function that may be associated with risk of acute respiratory events (ARE). Methods: Data from 6-min walk testing (6MWT) in COPDGene were used to calculate the chronotropic index (CI) [(HR immediately post 6MWT – resting HR)/((220 – age) – resting HR)] and HRR at 1 min after 6MWT completion. We used zero-inflated negative binomial regression to test associations of CI and HRR with rates of any ARE (requiring steroids and/or antibiotics) and severe ARE (requiring emergency department visit or hospitalization), among all participants and in spirometry subgroups (normal, chronic obstructive pulmonary disease [COPD], and preserved ratio with impaired spirometry). Results: Among 4, 484 participants, mean follow-up time was 4.1 years, and 1, 966 had COPD. Among all participants, CI-6MWT was not associated with rate of any ARE [adjusted incidence rate ratio (aIRR) 0.98 (0.95–1.01)], but higher CI-6MWT was associated with lower rate of severe ARE [0.95 (0.92–0.99)]. Higher HRR was associated with a lower rate of both any ARE [0.97 (0.95–0.99)] and severe ARE [0.95 (0.92–0.98)]. Results were similar in the COPD spirometry subgroup. Conclusion: Heart rate measures derived from 6MWT tests may have utility in predicting risk of acute respiratory events and COPD exacerbations. Highlights: Abnormal heart rate responses to exercise are common in COPD. Heart rate responses are one measure of autonomic function. Autonomic dysfunction may be a risk factor for acute respiratory events. Better heart rate responses were associated with lower rates of respiratory events.